O uso das Tecnologias de Informação e Comunicação (TIC) na disseminação da informação religiosa - Santos, Jussara Ventura dos (2014)
Analyzes the use of information and communication technologies (ICT) as an enabling tool in information dissemination of religious matrix in cyberspace process. Aims to a) propose a concept for religious information matrix b) describe the informational devices, ICTs used by IEADPB and c) seize the motivation of using these devices in the technical processing of information dissemination that Institution Religious. Warp presents a methodology based on the principles of ethnography to design during the study. Defines how the research universe adpb portal whose institution maintains the Evangelical Assembly of God Church in Paraíba - IEADPB. Identifying the portal through analysis of characteristics, as a virtual community derivative. In his theoretical framework presents themes such as the centrality of ICTs in the information society, which is a historical / conceptual survey of the term giving lists typology focuses on some of the most popular technologies today. Proposes the construction of the concept of religious information matrix relying on theoretical dealing philosophy and the theory of concept example of Deleuze and Guattari (philosophy) and Dahlberg (theory) . This chapter presents the relevant aspects regarding the information in a pluralistic society and how to understand the religious phenomenon as a source of information from this line of thought to initiate its proposed conceptual construction exposing its plane of immanence. Explains the emergence of ciber-religião as subtopics of this chapter contains reflections about cyberculture and the transition period between traditional and virtual, as well as ascertains the presence of religious matrix of information in virtual environments. The process of data collection makes use of an arrangement consisting of two classical instruments, the mixed questionnaire and semi-structured interviews in conjunction with direct observation. At the stage of data analysis uses the triangulation of them to understand the development of the portal in three perspectives: the idealization of the project, their creative process and management. Weaves the final product considerations of the knowledge acquired during the survey, answering the initial research questions, particularly highlighting the relevance of this study to society, information science and knowledge as a whole. Emphasizes the (in)visibility given to religious information in public spaces. Exposes the development of the information systems IEADPB